(untitled) (Swiss Medical Weekly, 2001)
The recent genetic discoveries in CP support the hypothesis that inappropriate intrapancreatic activation of zymogens by trypsin results in autodigestion and pancreatitis. Two different protective mechanisms prevent activation of the pancreatic digestive enzyme cascade. First, SPINK1 inhibits up to 20% of potential trypsin activity and, second, trypsin itself activates trypsin-like enzymes readily degrading trypsinogen and other zymogens. Pancreatitis may therefore be the result of an imbalance between proteases and their inhibitors within the pancreatic parenchyma. The discovery of PRSS1 mutations in families with CP was the first breakthrough in the understanding of the underlying genetic mechanisms. Enhanced trypsinogen activation may be the common initiating step in pancreatitis caused by these mutations. The discovery of SPINK1 mutations underlines the importance of the protease inhibitor system in the pathogenesis of CP. Thus, gain-of-function in the cationic trypsinogen resulting in an enhanced autoactivation, or loss-of-function mutations in SPINK1 leading to decreased inhibitory capacity, may similarly disturb the delicate intrapancreatic balance of proteases and their inhibitors. The recent findings of SPINK1, CFTR, and PRSS1 mutations in CP patients without a family history have challenged the concept of idiopathic CP as a non-genetic disorder and the differentiation between HP and ICP. There is a clear mode of autosomal dominant inheritance for some mutations (R122H, N291, possibly MIT), whereas the inheritance pattern (autosomal recessive, complex, or modifying) of other mutations (A16V, N34S) is controverted or unknown. The lack of mutations in the above-mentioned genes in many patients suggests that CP may also be caused by genetic alterations in yet unidentified genes. Evaluation of CP patients without an obvious predisposing factor, e.g. alcohol abuse, should include genetic testing even in the absence of a family history of pancreatitis. Finally, identification of further disease-causing genes will create a better understanding of pathogenesis and may help to develop specific preventive and therapeutic strategies.